Public International Law and the Regulation of Diplomatic Immunity in the Fight against Corruption - Kenneth K Mwenda (Pretoria University Law Press (PULP), 2011)
Public International Law and the Regulation of Diplomatic Immunity in the Fight against Corruption by Kenneth K Mwenda 2011 ISBN: 978-0-9869857-9-9 Pages: 212 Print version: Available Electronic version: Free PDF available